Differentiation of human hemoglobin at high altitudes - Aste Salazar, Humberto (2015)
A study has been carried out on the possibility that chronic hypoxia, to which the subject who are born and live at great altitudes are submitted, could produce high values of fetal hemoglobin. Normal new borns and normal adult subjects from Lima (150 meters over sea level), Oroya (3,726 mts.), Morocoha (4,540 mt.) and Ticlio (4,826 mts.), were studied. To measure the amount of fetal hemoglobin two methods were employed: "proportion of alkaline - denaturation" and the "1 minute-residue". At great altitdes the amount of Hb F fall between the normal range at sea level. It was established that there is no difference n the "proportion of alkaline-denaturation" of the Hb, between the subjects (newborns and adults) living at sea level and those living at great altitutdes, or of the few patients with chronic "soroche". It is postulated that the hypoxia of great altitudes does not stimulate the production of Hb F either in the native or in the newborn, or in Monge's disease patients, regardless of the oxygen insaturation of arterial blood, and normal adult Hb is produced almost exclusively. The basic problem exits in the supply of oxygen to the tissues. A deviation to the right of the oxygen dissociation curve of oxi-Hb would be of great benefit in that process, as there is need of less fall of the arterial pO2 to supply the tissues with the same amount of oxygen than at sea level, specially if the increased quantity of Hb present is considered.